Metformin and Fibrosis: A Review of Existing Evidence and Mechanisms - Maoyan Wu; Huiwen Xu; Jingyu Liu; Xiaozhen Tan; Shengrong Wan; Man Guo; Yang Long; Yong Xu (Journal of Diabetes Research)
Fibrosis is a physiological response to organ injury and is characterized by the excessive deposition of connective tissue components in an organ, which results in the disruption of physiological architecture and organ remodeling, ultimately leading to organ failure and death. Fibrosis in the lung, kidney, and liver accounts for a substantial proportion of the global burden of disability and mortality. To date, there are no effective therapeutic strategies for controlling fibrosis. A class of metabolically targeted chemicals, such as adenosine monophosphate-activated protein kinase (AMPK) activators and peroxisome proliferator-activated receptor (PPAR) agonists, shows strong potential in fighting fibrosis. Metformin, which is a potent AMPK activator and is the only recommended first-line drug for the treatment of type 2 diabetes, has emerged as a promising method of fibrosis reduction or reversion. In this review, we first summarize the key experimental and clinical studies that have specifically investigated the effects of metformin on organ fibrosis. Then, we discuss the mechanisms involved in mediating the antifibrotic effects of metformin in depth.